2005
DOI: 10.1523/jneurosci.4619-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Medial Septal GABAergic Neurons Express the Somatostatin sst2AReceptor: Functional Consequences on Unit Firing and Hippocampal Theta

Abstract: GABAergic septohippocampal neurons play a major role in the generation of hippocampal theta rhythm, but modulatory factors intervening in this function are poorly documented. The neuropeptide somatostatin (SST) may be one of these factors, because nearly all hippocampal GABAergic neurons projecting to the medial septum/diagonal band of Broca (MS-DB) express SST. In this study, we took advantage of the high and selective expression of the SST receptor sst 2A in MS-DB to examine its possible role on theta-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 58 publications
6
40
0
3
Order By: Relevance
“…The distribution pattern of GAD67 positive neurons we observed in the medial septum was similar to that described by (Bassant et al, 2005).…”
Section: Antibody Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…The distribution pattern of GAD67 positive neurons we observed in the medial septum was similar to that described by (Bassant et al, 2005).…”
Section: Antibody Characterizationsupporting
confidence: 88%
“…Indeed, such studies are the goal of our current and future research (e.g. Ma et al, 2009b;Bassant et al, 2005;Simon et al, 2006).…”
Section: Implications For Understanding Medial Septum Functionmentioning
confidence: 99%
“…The primary antibodies used in this study were the following: rabbit polyclonal antibodies against ␤1 adrenergic receptor (Jane-wit et al, 2007) and ␤2 adrenergic receptor (Guo and Li, 2007); mouse monoclonal antibodies against calretinin (Lagace et al, 2007), calbindin (Celio, 1990), cholecystokinin (Pawelzik, 2002), and parvalbumin (Celio, 1990); sheep polyclonal antibody against neuropeptide Y (Jinno and Kosaka, 2006); and goat polyclonal antibody against somatostatin (Bassant et al, 2005). Further details regarding each of the primary antibodies used in this study are given below and in Table 1.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Using juxtacellular recording and labeling with neurobiotin, it was shown that PV immunoreactive (PVϩ) neurons exhibited bursting activity tightly coupled to hippocampal theta waves (Borhegyi et al, 2004;Bassant et al, 2005). RB activity was also observed in GABAergic neurons found to express glutamic acid decarboxylase (GAD) but not PV (Bassant et al, 2005). These data demonstrated undoubtedly that the GABAergic MS-DB neurons are capable of displaying bursting activity at theta frequency.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous in vivo studies attempted to establish the nature of the RB septal neurons, but, until recently, the correlation between neurochemical phenotypes and firing properties remained indirect. Using juxtacellular recording and labeling with neurobiotin, it was shown that PV immunoreactive (PVϩ) neurons exhibited bursting activity tightly coupled to hippocampal theta waves (Borhegyi et al, 2004;Bassant et al, 2005). RB activity was also observed in GABAergic neurons found to express glutamic acid decarboxylase (GAD) but not PV (Bassant et al, 2005).…”
Section: Introductionmentioning
confidence: 99%